Maternal food literacy among posyandu cadres: A community-based assessment in rural South Sulawesi, Indonesia - Bulu, Rifaah Mahmudah; Febrianti, Devy; Ananda, Rusda (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2026)
Food literacy has increasingly been recognized as an important determinant of healthy dietary behavior, yet limited evidence is available on food literacy among mothers serving as Posyandu cadres in rural stunting-locus communities, particularly within interventions integrating nutrition education and practical growth-monitoring skills. This study aimed to assess the food-literacy level of Posyandu cadres and strengthen their capacity through balanced-nutrition education based on the Indonesian Isi Piringku guideline, healthy-lifestyle promotion, and practical child anthropometric measurement. A descriptive community-based intervention using an educational-participatory approach was conducted in Lampenai Village, Luwu Timur Regency, South Sulawesi, Indonesia, involving 20 Posyandu cadres. Food literacy was assessed before training using a 19-item questionnaire adapted from the Eating and Food Literacy Behaviors Questionnaire. Training was delivered through interactive lectures, discussions, case studies, healthy-menu planning, and demonstrations of standardized weight and height measurement. The findings showed that 14 cadres (70%) had good food literacy, whereas six cadres (30%) had moderate food literacy. These findings indicate that most cadres possessed an adequate foundation for applying food-related information, although additional capacity strengthening remains necessary for some participants. Integrating food-literacy education, practical nutrition skills, and anthropometric competencies within Posyandu activities may strengthen cadres' roles as community nutrition agents and support sustainable village-level stunting-prevention strategies.